2012 IEEE 8th International Conference on E-Science 2012
DOI: 10.1109/escience.2012.6404482
|View full text |Cite
|
Sign up to set email alerts
|

Why workflows break — Understanding and combating decay in Taverna workflows

Abstract: Workflows provide a popular means for preserving scientific methods by explicitly encoding their process. However, some of them are subject to a decay in their ability to be reexecuted or reproduce the same results over time, largely due to the volatility of the resources required for workflow executions. This paper provides an analysis of the root causes of workflow decay based on an empirical study of a collection of Taverna workflows from the myExperiment repository. Although our analysis was based on a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…Zhao et al [12] in their paper investigate the cause of the so called workflow decay, which means that year by year the ability and success of the re-execution of any workflow significantly reduces. They examined 92 Taverna workflows submitted in the period from 2007 to 2012 and found four major causes: 1.…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et al [12] in their paper investigate the cause of the so called workflow decay, which means that year by year the ability and success of the re-execution of any workflow significantly reduces. They examined 92 Taverna workflows submitted in the period from 2007 to 2012 and found four major causes: 1.…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et al [23] in their paper investigated the cause of the so called workflow decay. They examined 92 Taverna workflows submitted in the period between 2007 and 2012 and found four major causes: 1) Missing volatile third party resources 2) Missing example data 3) Missing execution environment (requirement of special local services) and 4) Insufficient descriptions about workflows.…”
Section: Requirementsmentioning
confidence: 99%
“…Unfortunately experiences have showed that many workflows failed on occasion of a later re-execution. Zhao et al [23] [11] investigated the main purposes of the so-called workflow decay, which means that year by year the ability and success of the re-execution of any workflow significantly reduces. They found four main causes which have prevented the re-execution: 1. the missing environmental parameters, 2. missing third party resources; 3. missing descriptions about the workflows; 4. the missing samples of the experiments or the inputs and outputs of the workflows.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [9] in their paper investigate the cause of the so called workflow decay, which means that year by year the ability and success of the re-execution of any workflow significantly reduces. They examined 92 Taverna workflows submitted in the period from 2007 to 2012 and found four major causes: 1.…”
Section: State Of the Artmentioning
confidence: 99%